2018
DOI: 10.1038/s41598-018-36193-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of HIV on executive function and verbal fluency in Cameroon

Abstract: HIV-associated neurocognitive disorders (HAND) are frequently associated with impaired executive function and verbal fluency. Given limited knowledge concerning HAND in Sub-Saharan-Africa and lack of Cameroonian adult neuropsychological (NP) test norms, we administered four executive function [Halstead Category Test (HCT), Wisconsin Card Sorting Test (WCST), Color Trails-II (CTT2), and Stroop Color-Word-Interference (SCWT)] and three verbal fluency (Category, Action, and Letter Fluency) tests to 742 adult Came… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
14
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 89 publications
2
14
1
Order By: Relevance
“…The effect sizes for individual NP tests and domain T-scores in our studies are in the same ranges as effect sizes observed in some large US cohort studies (Maki et al, 2015;Rubin et al, 2015). The proportion of cases in this study with impairment based on individual tests or domain T-scores (17-23%) is in line with our previous findings (Kanmogne et al, 2018;Kanmogne et al, 2010;Njamnshi et al, 2009;Njamnshi et al, 2008) and some previously reported prevalence of HAND in Nigeria (21.5%) (Yusuf et al, 2017) and South Africa (23%) (Joska, Fincham, Stein, Paul, & Seedat, 2010). However, these are much lower than HAND prevalence reported among HIV-infected adults in other studies in Nigeria, China, and India (26-28%) (Jumare et al, 2019;Royal et al, 2012); South Africa (36-53%) (Joska et al, 2011;Mogambery, Dawood, Wilson, & Moodley, 2017), Botswana (37-38%) (Lawler et al, 2011), Zambia (34-35%) (Kabuba et al, 2017), Uganda (38-64%) (Nakku, Kinyanda, & Hoskins, 2013;Sacktor et al, 2019;Yechoor et al, 2016), and the United States (36-45%) (Heaton et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The effect sizes for individual NP tests and domain T-scores in our studies are in the same ranges as effect sizes observed in some large US cohort studies (Maki et al, 2015;Rubin et al, 2015). The proportion of cases in this study with impairment based on individual tests or domain T-scores (17-23%) is in line with our previous findings (Kanmogne et al, 2018;Kanmogne et al, 2010;Njamnshi et al, 2009;Njamnshi et al, 2008) and some previously reported prevalence of HAND in Nigeria (21.5%) (Yusuf et al, 2017) and South Africa (23%) (Joska, Fincham, Stein, Paul, & Seedat, 2010). However, these are much lower than HAND prevalence reported among HIV-infected adults in other studies in Nigeria, China, and India (26-28%) (Jumare et al, 2019;Royal et al, 2012); South Africa (36-53%) (Joska et al, 2011;Mogambery, Dawood, Wilson, & Moodley, 2017), Botswana (37-38%) (Lawler et al, 2011), Zambia (34-35%) (Kabuba et al, 2017), Uganda (38-64%) (Nakku, Kinyanda, & Hoskins, 2013;Sacktor et al, 2019;Yechoor et al, 2016), and the United States (36-45%) (Heaton et al, 2015).…”
Section: Discussionsupporting
confidence: 91%
“…Data showed no difference in learning or memory based on HIV genotype but compared to subjects infected with AG-Plus and non-AG HIV-1, subjects infected with AG viruses had higher functioning on the overall composite attention/WM T-scores. Therefore, previous findings of reduced inflammation with AG viruses and Tat.AG (Bhargavan & Kanmogne, 2018;Woollard et al, 2014) may be associated with less impairment in executive function (Kanmogne et al, 2018) and reduced deficits in attention/ WM among subjects harboring AG viruses, compared to subjects infected with other HIV genotypes. Our subsequent studies will determine whether there is a correlation between viral genotype, systemic inflammation, and risk of other NCIs in these subjects.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…At the most basic level, HIV-1 seropositive individuals (Minassian et al 2013) display prominent alterations in preattentive processes (sensorimotor gating); deficits which have been translationally modeled across multiple biological systems used to model HAND (e.g., HIV-1 Tg rat: Moran et al 2013, McLaurin et al 2017; stereotaxic injections of HIV-1 viral proteins: Fitting et al 2006aFitting et al , 2006b; gp120 transgenic mice: Henry et al 2014, Bachis et al 2016; Tat transgenic mice: Paris et al 2015). Alterations in the core components of cognitive function, including key components of both representational knowledge (e.g., attention, long-term episodic memory) and executive function (e.g., flexibility, inhibition), have also been reported in clinical (e.g., Heaton et al 2011;Maki et al 2015;Kanmogne et al 2018) and preclinical (e.g., Lashomb et al 2009;Moran et al 2014;Repunte-Canonigo et al 2014;McLaurin et al 2018McLaurin et al , 2019a studies. Given the componential relationship between neurocognitive functions, examining the effect of SE on the core components of cognitive function (i.e., preattentive processes, stimulus-response learning, sustained attention, and selective attention) will provide one critical test of its therapeutic potential for HAND in the post-cART era.…”
Section: Introductionmentioning
confidence: 99%
“…www.nature.com/scientificreports/ Stroop color naming and word reading speed 40 . The Stroop test was administered over 45 s as we previously described 30 , with scores consisting of the total number of words read and total number of colors correctly identified and named. This test measures cognitive processing, mental speed and mental control.…”
Section: Discussionmentioning
confidence: 99%